2016
DOI: 10.3389/fpsyg.2016.01126
|View full text |Cite
|
Sign up to set email alerts
|

Structural Validity of the Pittsburgh Sleep Quality Index in Chinese Undergraduate Students

Abstract: The purpose of this study was to examine the structural validity of the Pittsburgh Sleep Quality Index (PSQI) in Chinese undergraduate students. A cross-sectional questionnaire survey with 631 Chinese undergraduate students was conducted, and the questionnaire package included a measure of demographic characteristics, PSQI, Chinese editions of Center for Epidemiologic Studies-Depression, State- Trait Anxiety Inventory, Rumination Response Scale, and Perceived Social Support Scale. Results showed that the item … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 30 publications
4
86
0
2
Order By: Relevance
“…Comparably, in the study of Zhu, Xie, Park, and Kapella () who adapted the Chinese Version of PSQI in patients with type 2 diabetes, Cronbach's α was 0.78. Guo et al () evaluated the structural validity of the PSQI in Chinese undergraduate students and reported Cronbach's α of 0.91. In addition to construct validity, good convergent validity was confirmed by significant correlation between the PSQI global score and MAF fatigue score.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparably, in the study of Zhu, Xie, Park, and Kapella () who adapted the Chinese Version of PSQI in patients with type 2 diabetes, Cronbach's α was 0.78. Guo et al () evaluated the structural validity of the PSQI in Chinese undergraduate students and reported Cronbach's α of 0.91. In addition to construct validity, good convergent validity was confirmed by significant correlation between the PSQI global score and MAF fatigue score.…”
Section: Discussionmentioning
confidence: 99%
“…The best factor structure of PSQI varies among previous studies (Koh, Lim, Chia, & Lim, ; Qiu et al, ; Raniti, Waloszek, Schwartz, Allen, & Trinder, ; de la Vega et al, ), probably due to divergent diagnosis of the subjects, inconsistent statistical methodology and different country of origin. Many studies supported a two‐factor solution, which can be more representative of the PSQI's scale structure than other models (Guo et al, ; Qiu et al, ). Guo et al () investigated the factor structure of the PSQI in a cohort of 631 undergraduate students and reported that a two‐factor model could best fit the data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations